Postinjury treatment with magnesium sulfate attenuates neuropathic pains following spinal cord injury in male rats. Issue 3 (April 2015) - Farsi, Leila; Afshari, Khashayar; Keshavarz, Mansoor; NaghibZadeh, Maryam; Memari, Fereidoon; Norouzi-Javidan, Abbas
Abstract : Spinal cord injury (SCI) has a number of severe and disabling consequences including chronic pain. Approximately 40% of patients experience neuropathic pain, which appears to be persistent. Previous studies have demonstrated the neuroprotective effects of magnesium sulfate (MgSO4 ). We aimed to investigate the effect of MgSO4 on neuropathic pains following SCI in male rats. Thirty-two adult male rats (weight 300–350 g) were used. After laminectomy, a complete SCI was induced by compression of the spinal cord for 1 min with an aneurysm clip. A single dose of 300 or 600 mg/kg MgSO4 was injected intraperitoneally. Tail-flick latency and acetone drop test scores were evaluated before surgery and once a week for 4 weeks after surgery. Rats in groups SCI+Mg300 and SCI+Mg600 showed significantly higher mean tail-flick latencies and lower mean scores in the acetone test compared with those in the SCI+veh group 4 weeks after surgery ( P <0.05). These findings revealed that systemic single-dose administration of MgSO4 can attenuate thermal hyperalgesia and cold allodynia induced by SCI in rats.